Strategi Orangtua dalam Mengajarkan Membaca dan Menulis Anak pada Masa Pandemi Covid 19 - Yuri Apriliana; Adisel Adisel; Septi Fitriana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The aim of this research is to know the parent’s strategy to teach the children in reading and writing at the covid era. The case study of the children of the third one at Rt 22 Rw 08 Panorama bengkulu. The method of theresearch that used is the field research by descriptive Qualytative approach. the tehnique of collected data, is observation, imterview and public documentation. the problem formulation in language of the research is how the strategy that used of parents in teaching of reading and writing The children at the Rt 22 Rw 08 panorama singaranpati bengkulu The result of this research is the re are some method that used of the parents in teaching reading . of the students of Rt 22 Rw 08 panorama. they are in individual studying, integreted studying, deduction studying, discovery leasrning, studying strategy to the student’s orientation activity : in teaching writing are strstegy rkspository, studying kooperative jigsaw, individual studying strategy to the student’s activity orientation an deduction. Keywords : Parent’s Strategy, Children Read and Write